Experimental evaluation of the usage of ad hoc networks as stubs for multiservice networks - Sarrô, Rafael (2012)
This paper describes an experimental evaluation of a multiservice ad hoc network, aimed to be interconnected with an infrastructure, operator-managed network. This network supports the efficient delivery of services, unicast and multicast, legacy and multimedia, to users connected in the ad hoc network. It contains the following functionalities: routing and delivery of unicast and multicast services; distributed QoS mechanisms to support service differentiation and resource control responsive to node mobility; security, charging, and rewarding mechanisms to ensure the correct behaviour of the users in the ad hoc network. This paper experimentally evaluates the performance of multiple mechanisms, and the influence and performance penalty introduced in the network, with the incremental inclusion of new functionalities. The performance results obtained in the different real scenarios may question the real usage of ad-hoc networks for more than a minimal number of hops with such a large number of functionalities deployed.